A novel concept for optimal operation of multi-swap stations serving electric metrobuses - Cicek, Alper; Karakus, Furkan; Erdinc, Ozan (ELSEVIER, 2025)
Due to the carbon emissions produced by the conventional transportation sector's use of fossil fuels, transportation vehicles are considered one of the leading contributors to global climate change. Additionally, in metropolises like Istanbul/T & uuml;rkiye, traffic congestion is one of the most significant issues. Taking these factors into account, there is a need to promote the use of public transportation vehicles and electrification of the system. This study focuses on the optimal energy management of multi-swap stations (MSSs) with photovoltaic (PV) systems serving an electric metrobus (EM) line. The presented framework is modeled using a mixed-integer linear programming (MILP) approach. In this system, when the batteries of the EMs on the route are running low, they can come to the stations where the swap operation can be performed, allowing them to exchange their batteries within the passenger boarding and disembarking times. Besides, the power transferring between batteries at swap stations is considered, which helps ensure flexible operation. The PV systems can be utilized for battery charging, and surplus energy can be sold to the power grid. Various test studies are conducted using data from the Istanbul Z34 metrobus route in this research. According to the results obtained from the study, the proposed structure demonstrates the effective operation of swap stations serving EMs. Doubling the PV capacity increased the profit to 6103 Turkish Liras (TL). In October, the highest energy selling revenue of 4791 TL was recorded due to elevated electricity prices. Inter-battery power transfer provided cost savings, with up to 50 TL saved in January, while prioritizing PV energy sales to the grid further reduced operating expenses.
Keywords: Energy management model; Metrobus; Multi-swap stations; Optimal operation; Renewable energy; DESIGN; Science & Technology - Other Topics; Energy & Fuels